2017
DOI: 10.2355/isijinternational.isijint-2017-320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on Surface Roughening in Stretch Forming of Steel Sheets

Abstract: Surface quality is an important requirement in outer automobile panels, and to obtain products with an excellent surface quality the development of surface roughening during press forming should be prevented. However, the influence of microstructures on surface roughening is not yet sufficiently understood, and thus it is difficult to control surface roughening during press forming. In this study, the mutual effect of the development of texture and the surface profile variation is examined in detail using two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The equivalent plastic strain was calculated by von Mises yield criterion, though the materials had some anisotropy ( Table 1). As in our previous study, 20) the development of surface roughening was observed after stopping the test at certain punch strokes, until necking occurred. After stopping the test at intervals, 25 mm square specimens were cut from the center part, where the most significant surface roughening could be observed.…”
Section: (1)supporting
confidence: 61%
See 4 more Smart Citations
“…The equivalent plastic strain was calculated by von Mises yield criterion, though the materials had some anisotropy ( Table 1). As in our previous study, 20) the development of surface roughening was observed after stopping the test at certain punch strokes, until necking occurred. After stopping the test at intervals, 25 mm square specimens were cut from the center part, where the most significant surface roughening could be observed.…”
Section: (1)supporting
confidence: 61%
“…13 depending on strain ratio is derived from the difference in deformation resistance between the neighboring grains. This result implies that the inhomogeneous deformations of polycrystalline grains are effected not only by the initial crystal orientations 20) but also by their deformation mode. Figure 15 shows a comparison between the experimental and calculated changes of the parameter P a during biaxial stretch forming.…”
Section: Numerical Simulation Of Surface Rougheningmentioning
confidence: 91%
See 3 more Smart Citations